Congenital Cytomegalovirus Infection As Lissencephaly - A Case Report - Kundu, Gopen Kumar; Akhter, Mohsina; Akhter, Shaheen; Rahman, Md Mizanur (Bangladesh Journal of Child Health, 2014)
DOI: http://dx.doi.org/10.3329/bjch.v38i1.20029 Bangladesh J Child Health 2014; VOL 38 (1) : 51-54